The Influence of Live Streaming, Influencer Marketing, and e-WOM on Skintific Repurchase Intention on Shopee - Juniati; Audita Nuvriasari (Economic and Business Horizon, 2026)
This study addresses the increasing importance of digital marketing strategies in online marketplaces and their impact on consumer repurchase behavior. With the rapid growth of e-commerce platforms, particularly Shopee, understanding the role of emergent promotional tools such as live streaming, influencer marketing, and Electronic Word of Mouth (E-WoM) is essential for brands seeking sustained consumer engagement. The primary objective of this research was to analyze the influence of live streaming, influencer marketing, and E-WoM on the repurchase intention of Skintific products on the Shopee marketplace. A total of 100 Shopee users in Yogyakarta who had previously purchased Skintific products were surveyed using a non probability sampling technique via online questionnaires. Instrument tests confirmed that all collected data were both valid and reliable. Classical assumption tests indicated normal data distribution and a regression model free from multicollinearity and heteroscedasticity. The results reveal that live streaming and E-WoM have positive and significant effects on repurchase intention, whereas influencer marketing does not exhibit a significant influence. These findings suggest that interactive and peer driven communication channels are more effective in fostering repeat purchase intentions in the context of online skincare products.